BANTUAN SUPERVISOR KEPADA GURU DALAM MENGATASI EMOSIONAL PROBLEM - MUHNIANSYAH ARASYID MAHANI (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2025)
The life of a teacher is a unique experience that constantly grapples with complex problems. This is understandable because a teacher's life encompasses two realms: the school and the community, including the teacher's own family. Within these realms, teachers are inextricably linked to challenges that must be faced and resolved effectively. Furthermore, internal problems are sometimes, and can even be, more serious, and can have more serious consequences. From this description, it can be said that